2012
DOI: 10.1021/jp3090638
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Collapse of Single-Walled Alumino-Silicate Nanotubes: Transformation Mechanisms and Morphology of the Resulting Lamellar Phases

Abstract: The thermally induced structural transformations are studied of three imogolite-type nanotube (NT) materials: (i) proper imogolite (IMO, (OH) 3 Al 2 O 3 SiOH) with outer surface covered by Al−OH−Al groups and inner surface lined by silanols); (ii) methyl-imogolite (Me-IMO, (OH) 3 Al 2 O 3 SiCH 3 ), in which the inner surface silanols have been replaced by methyl groups while the outer surface is unchanged, and (iii) the material Me-IMO-NH 2 , obtained by grafting the outer surface of Me-IMO with 3-aminopropyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…With IMO, previous work (Zanzottera et al 2012) has indeed shown the occlusion of some perchlorate anions coming from the synthesis batch, since molecular oxygen was released at high temperature during TG-mass analysis (Zanzottera et al 2012). During the synthesis of Fe-x-IMO, chloride ions likely replace (larger) perchlorate anions, thereby decreasing the final a value.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…With IMO, previous work (Zanzottera et al 2012) has indeed shown the occlusion of some perchlorate anions coming from the synthesis batch, since molecular oxygen was released at high temperature during TG-mass analysis (Zanzottera et al 2012). During the synthesis of Fe-x-IMO, chloride ions likely replace (larger) perchlorate anions, thereby decreasing the final a value.…”
Section: Resultsmentioning
confidence: 93%
“…To determine Brunauer-Emmett-Teller specific surface area (BET SSA) and porous volume values reported in Table 1, N 2 isotherms were measured at 77 K on samples previously outgassed at 523 K, in order to remove water and other atmospheric contaminants, still preserving NT structure (MacKenzie et al 1989;Zanzottera et al 2012). Non-local density functional theory method (NL-DFT) was used to determine pores size distributions (PSDs), by means of an N 2 -silica kernel for cylindrical pores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Finally, both inner and outer hydroxylated surfaces offer interesting possibilities for surface functionalization. INTs can thus be rendered amphiphilic by replacing their inner silanol or germanol moiety by a functionalized one, 15 or by grafting molecular compounds on the outer aluminum wall. [15][16][17][18] Whatever the nature (SW or DW) or the nanotube nominal composition (OH) 3 Bundling is analyzed thanks to X-ray scattering (XRS) experiments.…”
Section: +mentioning
confidence: 99%
“…INTs can thus be rendered amphiphilic by replacing their inner silanol or germanol moiety by a functionalized one, 15 or by grafting molecular compounds on the outer aluminum wall. [15][16][17][18] Whatever the nature (SW or DW) or the nanotube nominal composition (OH) 3 Bundling is analyzed thanks to X-ray scattering (XRS) experiments. Our experiments and their analysis allow us to propose the first phase diagram for the bundle assembling of metal-oxide imogolite nanotubes.…”
Section: +mentioning
confidence: 99%